The political economy of Chinese finance - Choi, Jongmoo Jay, 1945-; Powers, Michael R.; Zhang, Xiaotian Tina (International finance review ;, 2016)
Volume 17 of International Finance Review focuses on a variety of issues relating to the political economy of Chinese finance, including: the pattern of government ownership and control of Chinese firms; the role of government in corporate governance of industrial and financial firms; the interaction of culture, law and institutions in Chinese governance systems; corporate social responsibility, stakeholders and sustainable growth; the effect of political connections on corporate performance and society; privatization, IPOs, exchange listing and firm valuation; the role of government in banking and financial markets; practice of corporate risk management and insurance; foreign-exchange policy and its effect on firms and markets; foreign direct and portfolio investments in China; international investments and operations of Chinese firms; Chinese economic relations with the US and other countries.